Biomarker and Isotopic Composition of Seep Carbonates Record Environmental Conditions in Two Arctic Methane Seeps - Yao, Haoyi; Panieri, Giuliana; Lehmann, Moritz F.; Himmler, Tobias; Niemann, Helge (Frontiers in Earth Science, 2021)
Present-day activity of cold-seeps in the ocean is evident from direct observations of methane emanating from the seafloor, the presence of chemosynthetic organisms, or the quantification of gas concentrations in the water column and pore water solutes. Verifying past cold seep activity and biogeochemical characteristics is more challenging but may be reconstructed from proxy records of authigenic seep carbonates. Here, we investigated the lipid-biomarker inventory, carbonate minerology, and stable carbon and oxygen isotope compositions of seep-associated carbonates from two active Arctic methane seeps, located to the northwest (Vestnesa Ridge; ~1200 m water depth) and south (Storfjordrenna; ~380 m water depth) offshore Svalbard. The aragonite-dominated mineralogy of all but one carbonate sample indicate precipitation close to the seafloor in an environment characterized by high rates of sulfate-dependent anaerobic oxidation of methane (AOM). In contrast, Mg-calcite rich nodules sampled in sediments of Storfjordrenna appear to have formed at the sulfate-methane-transition zone deeper within the sediment at lower rates of AOM. AOM activity at the time of carbonate precipitation is indicated by the 13C-depleted isotope signature of the carbonates (−20 to −30‰ VPDB), as well as high concentrations of 13C-depleted lipid biomarkers diagnostic for anaerobic methanotrophic archaea (archaeol and sn2-hydroxyarchaeol) and sulfate-reducing bacteria (iso and anteiso-C15:0 fatty acids) in the carbonates. We also found 13C-depleted lipid biomarkers (diploptene and a 4-methyl sterol) that are diagnostic for bacteria mediating the aerobic oxidation of methane (MOx). This suggests that the spatial separation between AOM and MOx zones was relatively narrow at the time of carbonate formation, as is typical for high methane-flux regimes. The seep-associated carbonates also displayed relatively high δ18O values (4.5 to 5‰ VPDB), indicating the presence of 18O-enriched fluids during precipitation, possibly derived from disintegrated methane gas hydrates. Based on the combined isotopic evidence, we suggest that all the seep carbonates resulted from the anaerobic oxidation of methane during intense methane seepage. The seepage was likely associated to the destabilization of gas hydrates, which led to the ebullition of methane from the seafloor into the water column.